Types of Eating Disorder Prodrome in Adolescence: The Role of Decision Making in Childhood - Harrison, Amy; Francesconi, Marta; Flouri, Eirini (Frontiers in Psychology, 2022)
Psychiatric disorders like eating disorders (EDs) might be underpinned by differences in decision making. However, little previous research has investigated this potential relationship using longitudinal data. This study aimed to understand how components of decision making (delay aversion, risk adjustment, risk taking, quality of decision making and deliberation time) measured by the Cambridge Gambling Task in the UK’s Millennium Cohort Study (MCS; n=11,303; female=50.17%) at age 11 might explain clusters/types of ED prodrome involving body dissatisfaction, intention to lose weight, dietary restraint, excessive exercise and significant under/overweight measured in the MCS at age 14. Latent class analysis revealed two groups within the cohort: a non-prodromal eating pathology group, who were more likely to be of “average” weight, according to the UK90, with minimal disordered attitudes and behaviors in relation to eating and weight; and a second group with prodromal eating pathology, who had more body dissatisfaction, a desire to lose weight, were using dietary restriction and exercise to influence weight and were more likely to be “overweight” according to the UK90 (Cole et al., 1995). Logistic regression showed that, after adjustment for confounding, higher risk-taking scores were associated with a 60% greater probability of being in the prodromal eating pathology group (b=0.47, OR=1.60, p<0.01), and higher scores on quality of decision making were associated with a 30% lower probability of being in the prodromal eating pathology group (b=-0.34, OR=0.70, p<0.05). Helping young people to engage in moderate risk taking and improving decision making might reduce the later presence of ED prodromes.